Becoming a Young Breadwinner? The Education, Employment and Training Trajectories of Young Fathers. Issue 1 (26th October 2015) - Neale, Bren; Davies, Laura
Abstract : The entry into fatherhood is a major life course transition involving the acquisition of new adult roles and responsibilities. This transition is rarely planned for young fathers, and may involve a range of challenges, not least their capacity to provide materially and financially for their child. Drawing on a Qualitative Longitudinal study of young fathers in the UK, this article charts their very different pathways through education, training and employment, showing how these are shaped by a constellation of life circumstances. The implications for policy are considered in the light of a shifting landscape of welfare reform and 'austerity' measures.